Pengembangan Senam Aerobik DAKO (Dance, Kids And Enjoy) Di SD Negeri 69 Kota Tengah - Ningsi, Sri Novaria; Said, Hariadi; Tumaloto, Ella H (Universitas Negeri Gorontalo, 2025)
This study aims to create and develop Dako (Dance, Kids And Enjoy) aerobic gymnastics in rhythmic gymnastics learning for students of SDN 69 Kota Tengah which can be used to support learning so that students can more easily convey the material being taught. Dako (Dance, Kids And Enjoy) aerobic gymnastics also provides insight to students that Aerobic gymnastics can be used at every level of elementary school. This research is a type of research (RD) this research was developed using five steps of the ADDIE development model, namely 1). Analysis, 2). Design, 3). Development, 4). Implementation, 5). Evaluation. Data collection techniques used were interviews, observations and questionnaires. This study produced Dako (Dance, Kids And Enjoy) aerobic gymnastics in rhythmic gymnastics learning for students of SDN 69 Kota Tengah in the form of learning media in the form of guidebooks and videos which contain music, writing and pictures. Based on the validation that has been carried out by the researcher on 3 experts, namely: gymnastics experts, learning experts and multi-media experts, the interval value was 4 with a very feasible category. The validation results showed that the Dako (Dance, Kids And Enjoy) aerobic gymnastics development product in rhythmic gymnastics learning for students of SDN 69 Kota Tengah made by the researcher was feasible to be used in the rhythmic gymnastics learning process for students of SDN 69 Kota Tengah.